The Meaning of Tempo Magazine Cover in Semiotics by Charles Sanders Peirce - Sevtiany, Venny; Kurnia, Septiawan Santana (UPT Publikasi Ilmiah UNISBA, 2023)
In the September 16-22, 2019, edition of Tempo, the magazine cover was shown painting a picture of President Joko Widodo’s face with his long nose like a Pinocchio wooden doll. One year later, Tempo republished the magazine cover by displaying a picture of the same figure, namely Pinocchio. But this time in the background of the DPR plenary session on the 11-25 October 2020 edition. This study examines the sign's meaning, the repetition factor in the sign, and the attractiveness of the Tempo magazine cover. The qualitative research method used in this research is the semiotic approach of Charles Sanders Peirce. This research produces a representation of meaning on the two covers, a form of people’s disappointment in public officials for the discrepancy between their words and actions. The factor of repetition of the “Pinocchio” sign that occurs on both covers based on data and facts is found repeatedly. The attractiveness of the Tempo magazine cover includes characteristics, point of view, and target audience, and this attraction results in a business strategy for Tempo magazine.